Central bank independence: Where do we stand? - Osvald Vasicek; Natalie Uhrova; Lenka Dimitriou Janickova; Tomas Wroblowsky; Boris Navratil (Economies, 2023)
Central bank independence (CBI) has long been considered a key aspect of effective monetary policy, as it allows central banks to make decisions free from political interference. However, the global financial crisis of 2007-2008 and recent events such as the COVID-19 pandemic and armed conflict in Ukraine have threatened CBI. This article aims to examine the impact of these events on CBI in OECD member countries, both on a de jure and de facto level, using a variety of indicators. The results suggest that CBI has largely remained unchanged in most countries, but there is disturbing evidence of political interference in CBI in the Republic of Türkiye.
Keywords: 330; de jure independence; de facto independence; central bank